ursaPGx: a new R package to annotate pharmacogenetic star alleles using phased whole-genome sequencing data - Calendo, Gennaro; Kusic, Dara; Madzo, Jozef; Gharani, Neda; Scheinfeldt, Laura (Frontiers in Bioinformatics, 2024)
Long-read sequencing technologies offer new opportunities to generate high confidence phased whole genome sequencing data for robust pharmacogenetic annotation. Here we describe a new user-friendly R package, ursaPGx, designed to accept multi-sample phased whole genome sequencing data VCF input files and output star allele annotations for pharmacogenes annotated in PharmVar.